Prevention of Hypocritical Behavior and Its Perspective in Islamic Education - Nahar, Syamsu (Dinamika Ilmu: Jurnal Pendidikan, 2020)
Hypocritical behavior needs to be watched out for because it is symptomatic in the community, especially now with access to global relationships without any boundaries of place and time where it is associated through social media, people who are infected with this disease are very difficult to guess, can only be known with certain signs namely: lying, treasonous, broken promises, riya, like to slander and spread lies. The purpose of this study is to explore broadly regarding with detail concept of hypocricy from several vital point of views i.e. from Al-Qur’an, Hadith, and Islamic interpreters. Furthermore, it is also highly urgent to avoid ourselves and teenagers from being a hypocrite. Hence, recognizing signs and characteristics of hypocrites is also crucial in order for us to be more alert toward this issue. Many studies about hypocricy have been conducted by many researchers in various condition including education, politics, and so fort. In this study, hypocracy is also discussed from Islamic education perspective.